"Small farmer large field", a new model to developing and improving adoption of hybrid rice technology in Indonesia. (November 2019) - Widyastuti, Y; Satoto,; Rumanti, I A; Wibowo, B P; Ruskandar, A; Widyantoro,; Rachmawati,; Zaini, Z
Abstract: At present, the international market prefers to rice with some specific characters such as long slender shape, soft with 22-24% amylose content, a high percentage of head rice, and also aromatic. To fulfill rice with export standard, the farmers who involve have to apply good agricultural practices (GAP). Therefore need a high yielding variety, one of those varieties is hybrid rice variety possessing long slender shape, soft, a high percentage of head rice, and aromatic. Small Farmers, Large Field (SFLF) scheme was assumed précised and local specific for low land rice cultivation. This concept was integrated for farmers with small land holding to increase benefit collectively. The concept also integrated all cultivation system starting from planting up to marketing which was done together by some stakes holders. The objectives of this study are to (1) identify the hybrid rice productivity in large scale, (2) verify and validate the development of hybrid rice technology in small farmer large field's model, and (3) analyze the preference of farmers to hybrid rice varieties. The research activities consisted of SFLF approach by using hybrid rice varieties with Jarwo Super system in large scale. Adoption survey and preference test for the farmer in term of rice plant performance, quality of grain paddy and rice which was done simultaneously in subak Tajen, Penebel sub-district, Tabanan district, Bali province. Dem-farm was conducted at 50 ha with hybrid rice varieties from ICRR and private company. Average hybrid rice yield is about 7.5 ton/ha to 13.5 ton/ha. The results of participatory varietal selection showed that the yield potential, performance of the plant, tolerance to pest and disease, and quality of grain from hybrid rice varieties had a positive influence on farmers' preference.